2008
DOI: 10.1002/jbm.a.32308
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 expression of alginate‐encapsulated chondrocytes is stimulated by low cell density

Abstract: Recent research in tissue engineering for the treatment of cartilage defects have demonstrated that matrix-biomaterial, cell culture conditions, and cytokine-related factors influence the chondrogenic differentiation pattern, especially for the expression of matrix genes. However, little is known about the impact of cell seeding density in a three-dimensional environment on the key chondrogenic transcription factor Sox9. Here we investigated, whether the cell concentration of alginate encapsulated chondrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…A variability of collagen II distribution in animals was also seen by Bernstein et al [23]. Another publication by Barley et al [133] reported an increased staining of collagen II and a decreased staining of collagen I in normal cartilage.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A variability of collagen II distribution in animals was also seen by Bernstein et al [23]. Another publication by Barley et al [133] reported an increased staining of collagen II and a decreased staining of collagen I in normal cartilage.…”
Section: Discussionsupporting
confidence: 53%
“…The pig and notably the Göttingen Minipig (GM) is often used in articular cartilage research [5,17,23,24] and is also a common model for the study of regeneration of focal cartilage defects [7,25,26] but the transection of the ACL has rarely been performed in this species up to now [6]. For the articular cartilage research skeletal mature individuals are required as older pigs may mirror the human condition better, as OA is mostly an affliction of older people whether or not there were previous injuries [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted for approval of an autologous cell product by the European Medicines Agency (EMA), cell densities in this range were also used [7, 8]. However, there is still a debate as to whether an increased cell density can lead to better cartilage filling, better morphological structure biomechanical properties and/or a more favourable clinical outcome [9, 10]. Thus, there remains a crucial need for studies evaluating the efficacy and safety of different cell densities and product doses.…”
Section: Introductionmentioning
confidence: 99%
“…Using articular chondrocytes, high density 3D systems promote the formation of cartilaginous matrix and phenotypic stability [22]. In a variety of tissue engineering systems involving alginate, agarose, and fibrin scaffolds, it has been demonstrated that chondrocyte phenotype, matrix deposition, and mechanical properties depend on initial seeding density [23][27]. Significantly, in a study of cell concentration in alginate beads, SOX9 expression and sulfated glycosaminoglycan (GAG) production were upregulated in porcine ACs encapsulated at low density, compared with high density [23].…”
Section: Introductionmentioning
confidence: 99%